Experimental and comparative study of gamma radiation effects on Si-IGBT and SiC-JFET. Issue 9 (August 2015) - Tala-Ighil, B.; Trolet, J.-L.; Gualous, H.; Mary, P.; Lefebvre, S.
Abstract: This paper deals with an experimental study and a comparative study of the effects of total ionising dose of 60 Co gamma radiation on Si-IGBT and SiC-JFET. The response of the threshold voltage and the turn-on switching parameters are reported for both devices. Charge trapping in the gate oxide causes the decrease of the threshold voltage for Si-IGBT. The decrease of this parameter combined with the behaviour of Miller plateau during irradiation results in a decrease of the collector current rise-time, the collector-emitter voltage fall-time, and the turn-on switching energy and in an increase of the peak of the turn-on switching power and of the turn-on overshoot collector current. No changes in these parameters are observed for SiC-JFETs up to 2900 Gy with a dose rate of 2.80 Gy/h. This indicates that those SiC-JFETs have extremely high radiation resistance with respect to the TID effects compared to the Si-IGBTs. Highlights: A comparative study of TID effects on Si-IGBT and SiC-JFET is proposed. SiC-JFET shows higher radiation resistance with respect to the TID than the Si-IGBTs. Until 2900 Gy, SiC-JFET is not sensitive to TID when gate and drain are not biased during irradiation.